2006
DOI: 10.1007/s00277-006-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine, cytarabine, and mitoxantrone (FLAM) for the treatment of relapsed and refractory adult acute lymphoblastic leukemia. A phase study by the Polish Adult Leukemia Group (PALG)

Abstract: Outcome of adults with acute lymphoblastic leukemia (ALL) who fail to achieve complete remission (CR) or who relapse soon after initial response is poor. The goal of this phase II study by the Polish Adult Leukemia Group (PALG) was to evaluate safety and efficacy of a new salvage regimen (FLAM) consisting of sequential fludarabine, cytarabine, and mitoxantrone. Fifty patients were included with primary (n = 13) or secondary (n = 5) refractoriness, early (<12 months) first relapse (n = 15), first relapse after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 19 publications
1
9
0
2
Order By: Relevance
“…4,[13][14][15][16][17] The overall CR rate of 42% for the first salvage approach in the present study was within the range reported from other retrospective studies (31%-44%). [3][4][5][6] Clearly, remission rates depend on chemotherapy sensitivity, which is lower in early relapse compared with late relapse and lowest in patients with refractory disease after the first salvage approach.…”
Section: Discussionsupporting
confidence: 76%
“…4,[13][14][15][16][17] The overall CR rate of 42% for the first salvage approach in the present study was within the range reported from other retrospective studies (31%-44%). [3][4][5][6] Clearly, remission rates depend on chemotherapy sensitivity, which is lower in early relapse compared with late relapse and lowest in patients with refractory disease after the first salvage approach.…”
Section: Discussionsupporting
confidence: 76%
“…The chemotherapeutic drug AraC (1-b-D-arabinofuranosylcytosine, cytarabine), a deoxycytidine analog, is one of the most important antileukemic agents currently available for the treatment of AML [15,16], relapsed and refractory acute lymphoblastic leukemia [17][18][19], as well as a subset of malignant lymphoma [20]. Ara-C enters the cell mainly via equilibrative nucleoside transporter 1 (hENT1), and is phosphorylated to Ara-CMP by deoxycytidine kinase (dCK).…”
Section: Introductionmentioning
confidence: 99%
“…1-3), relapsed and refractory acute lymphoblastic leukemia (ALL; refs. [4][5][6], and other malignancies (7)(8)(9)(10). The chemotherapeutic efficacy of cytarabine varies dramatically between individuals.…”
Section: Introductionmentioning
confidence: 99%